Postcard Memories: A virtual / tangible memory sharing application for adults with early-stage dementia (ESD). Issue 1 (1st April 2020) - Ladly, Martha; Chadha, Kartikay
Dementia is a major cause of disability among older adults, with 50 million people worldwide living with the disease and 10 million new cases diagnosed each year. Postcard Memories is a web-based, virtual memory-sharing mobile application, designed to support individuals diagnosed with early-stage dementia (ESD), their families, friends and caregivers. The research and design methods employed argue the value and importance of elder‐computer interaction, and greater personalization, supporting and enhancing elder's engagement in both the virtual and physical mnemonics of memory sharing. The researchers implemented a two-stage study design, including formative and summative assessments of low- and high-fidelity prototypes, pre-, and post-testing questionnaires, patient and carer interviews and 'think-aloud' testing methodologies for interaction evaluation. Through quantitative and qualitative assessments this research demonstrates that the Postcard Memories application has potential benefits, including enhanced technical ability and hence self-confidence with new technologies; and enhanced interactions with family members, a promising outcome for those living with ESD.